Reactive oxygen species-responsive supramolecular deucravacitinib self-assembly polymer micelles alleviate psoriatic skin inflammation by reducing mitochondrial oxidative stress - Yao, Leiqing; Tian, Faming; Meng, Qinqin; Guo, Lu; Ma, Zhimiao; Hu, Ting; Liang, Qiongwen; Li, Zhengxiao (Frontiers in Immunology, 2024)
Introduction: The new topical formula is urgent needed to meet clinical needs for majority mild patients with psoriasis. Deucravacitinib exerts outstanding anti-psoriatic capacity as an oral JAK inhibitor; however, single therapy is insufficient to target the complicated psoriatic skin, including excessive reactive oxygen species (ROS) and persistent inflammation. To address this need, engineered smart nano-therapeutics hold potential for the topical delivery of deucravacitinib. Methods: hydrophobic Deucravacitinib was loaded into polyethylene glycol block-polypropylene sulphide (PEG-b-PPS) for transdermal delivery in the treatment of psoriasis. The oxidative stress model of HaCaT psoriasis was established by TNF-α and IL-17A in vitro. JC-1 assay, DCFH-DA staining and mtDNA copy number were utilized to assess mitochondrial function. 0.75% Carbopol®934 was incorporated into SPMs to produce hydrogels and Rhb was labeled to monitor penetration by Immunofluorescence. In vivo, we established IMQ-induced psoriatic model to evaluate therapeutic effect of Car@Deu@PEPS. Results: Deu@PEPS exerted anti-psoriatic effects by restoring mitochondrial DNA copy number and mitochondrial membrane potential in HaCaT. In vivo, Car@Deu@PEPS supramolecular micelle hydrogels had longer retention time in the dermis in the IMQ-induced ROS microenvironment. Topical application of Car@Deu@PEPS significantly restored the normal epidermal architecture of psoriatic skin with abrogation of splenomegaly in the IMQ-induced psoriatic dermatitis model. Car@Deu@PEPS inhibited STAT3 signaling cascade with a corresponding decrease in the levels of the differentiation and proliferative markers Keratin 17 and Cyclin D1, respectively. Meanwhile, Car@Deu@PEPS alleviated IMQ-induced ROS generation and subsequent NLRP3 inflammasome-mediated pyroptosis. Conclusion: Deu@PEPS exerts prominent anti-inflammatory and anti-oxidative effects, which may offers a more patient-acceptable therapy with fewer adverse effects compared with oral deucravacitinib.